The impact of financial distress on tax avoidance: An empirical analysis of the Vietnamese listed companies - Van Cuong Dang; Xuan Hang Tran (Cogent Business & Management, 2021)
This paper examines empirical evidence on the impact of financial distress on tax avoidance of 369 listed companies in Vietnam over the 2008-2020 period. Empirical results show the existence of a positive relationship between financial distress and tax avoidance for survey companies. In particular, the more the company is in danger of capital, the more tax avoidance it will take. The results also show that small companies will tend to avoid taxes more. Companies use debt leverage as a tax shield to help them reduce their tax obligations. Companies with large long-term assets are less likely to avoid taxes than companies with little long-term assets. And finally, the study also shows that the more the company has a big difference in book-tax, the more tax avoidance activities it will implement.
Keywords: 650; Financial distress; tax avoidance; Listed companies in Vietnam